(2u-1)(3+u)=0

Simple and best practice solution for (2u-1)(3+u)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2u-1)(3+u)=0 equation:


Simplifying
(2u + -1)(3 + u) = 0

Reorder the terms:
(-1 + 2u)(3 + u) = 0

Multiply (-1 + 2u) * (3 + u)
(-1(3 + u) + 2u * (3 + u)) = 0
((3 * -1 + u * -1) + 2u * (3 + u)) = 0
((-3 + -1u) + 2u * (3 + u)) = 0
(-3 + -1u + (3 * 2u + u * 2u)) = 0
(-3 + -1u + (6u + 2u2)) = 0

Combine like terms: -1u + 6u = 5u
(-3 + 5u + 2u2) = 0

Solving
-3 + 5u + 2u2 = 0

Solving for variable 'u'.

Factor a trinomial.
(-3 + -1u)(1 + -2u) = 0

Subproblem 1

Set the factor '(-3 + -1u)' equal to zero and attempt to solve: Simplifying -3 + -1u = 0 Solving -3 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1u = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1u = 0 + 3 -1u = 0 + 3 Combine like terms: 0 + 3 = 3 -1u = 3 Divide each side by '-1'. u = -3 Simplifying u = -3

Subproblem 2

Set the factor '(1 + -2u)' equal to zero and attempt to solve: Simplifying 1 + -2u = 0 Solving 1 + -2u = 0 Move all terms containing u to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2u = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2u = 0 + -1 -2u = 0 + -1 Combine like terms: 0 + -1 = -1 -2u = -1 Divide each side by '-2'. u = 0.5 Simplifying u = 0.5

Solution

u = {-3, 0.5}

See similar equations:

| (2y-7)(-6y^2+8y+2)= | | -x+5=-2x-8 | | 1-6x=-6x-2+3 | | 55=-5+3d | | 4x-8=56 | | 2.6=2(.8)+2w | | 8y^2-63y-1215=0 | | 8x-10=150 | | x^4-16x-80=0 | | 4x^3+2x-4=0 | | 5g-9=-74 | | p=3w+3L | | 16+(-4)= | | 0.1x=0.3y+0.2 | | (X-177)+196=278 | | Cosx-1=0 | | (1/(t-1))+(t/(6t-3)) | | -6-2(8p-6)=118 | | 15(-9)= | | 8x+14=6x | | 27(5+x)=189 | | -17-5= | | 18y=1/3 | | -6r+4=3 | | -58=-4y+10 | | 2(n-7)+9=9 | | x^4+6x-56=0 | | 5+3x=27-5x | | -19+(-9)= | | 1/6(3x-6)-3=7/12(x-6)-11/24 | | x^2-43x-340=0 | | 5y-15+3y=1 |

Equations solver categories